Global and European Labor Costs - Filip Abraham (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2001)
Multinational companies and national governments pay considerable attention to labor cost and labor productivity differentials across countries. This paper analyzes total and unit labor differentials for a group of European and non-European countries in the 1960-1998 period. It deals with (i) the magnitude of total labor cost differences (ii) the developments in unit labor cost and labor productivity (iii) the convergence process between countries with higher and lower labor costs.
Keywords: 330; Arbeitskosten; Arbeitsproduktivität; Vergleich; Entwicklungskonvergenz; EU-Staaten; OECD-Staaten